Membrane performance and application of ultrafiltration and nanofiltration to ethanol/water extract of Eucalyptus bark - Paula C. R. Pinto (2014)
The aim of this work is to promote the enrichment of an ethanolic extract of Eucalyptus globulus bark in polyphenolic compounds relatively to other compounds such as carbohydrates. Several flat sheet membranes were tested with water and ethanol solutions (52% v/v and 80% v/v) assessing to permeability. Rejections to gallic and tannic acids and maltose were evaluated for nanofiltration membranes and for the ultrafiltration membrane of lower cut-off. The dependence of permeability and rejection relative to ethanol percentage is discussed giving new insights about the membrane performance towards ethanol/water solutions. Among the tested membranes, two ultrafiltration (JW 30,000 Da and PLEAIDE 5000 Da) and one nanofiltration (SolSep 90801) membranes were selected to the concentration process of an ethanolic extract of Eucalyptus globulus bark produced at previously optimized conditions. The performance of the three membranes was evaluated concerning polyphenolic compounds and carbohydrate composition. The volume reduction factor was 1.76. JW membrane revealed the lowest total decrease on permeability (53%) relative to the initial. All the three membranes showed selective retention of polyphenolic compounds, however JW promoted the highest enrichment of formaldehyde-condensable tannins (fcT) and proanthocyanidins (Pac) (17% and 28%, respectively). The final composition of the retentate (in % weight/dry weight) was: TPC 39%, fcT 46%, Pac 38%, GalT 3.2% and TC 15%. The detailed sugar analysis revealed that some arabinose- and rhamnose-containing oligo/polysaccharides are preferentially retained, while those with glucose and galacturonic acid moieties are transported through the membrane to permeate stream. Finally, cleaning performance of membranes was evaluated and 80-100% flux recoveries were attained.